A Turn‐On Fluorescence Chemosensor for Cyanide in Aqueous Media Based on a Nucleophilic Addition Reaction. Issue 7 (8th March 2017) - Chen, Jie; Li, Wenting; Li, Qiao; Lin, Qi; Yao, Hong; Zhang, Youming; Wei, Taibao
Abstract: We synthesized a new cyanide (CN − ) chemosensorCX based on a nucleophilic addition reaction prompted by cyanide ion, which could be used for highly selective and sensitive fluorescence turn‐on detection of cyanide in aqueous media. TheCX showed selective fluorescence recognition for CN −, the miscellaneous competitive anions (F −, Cl −, Br −, I −, AcO −, H2 PO4 −, HSO4 −, ClO4 −, S 2 −, PO4 3−, CO3 2− and SCN − ) did not lead to any significant interference. The detection limit of the sensor towards CN − is 1.15 × 10 −7 molL −1 . The sensor has been successfully applied to estimate the cyanide ion in seeds of cherries. Test strips based onCX were fabricated, which could be used as a convenient and efficient CN − test kit to detect CN − in aqueous solution for "in‐the‐field" measurement. Abstract : In this work, a structurally simple anion sensor (CX ) for detection of cyanide anions based on a nucleophilic addition reaction was synthesized, which could be used for highly selective and sensitive fluorescence turn‐on detection of cyanide in aqueous media.